Mapeamento e gestão de processos aplicados na Pró-reitoria de Infraestrutura da Universidade Federal de Santa Maria - Schlosser, Andreia Lucila da Costa (2014)
In the current scenario, competitiveness is increasing, the globalization and technological innovations have brought many changes for organizations, requiring hem to evaluate for world production of assets and services standards. Educational institutions do not differ from this context due to the fact that they are engaged in adopting new practices to improve their services. In this context, observing the dayby- day organizational reality of the secretary of maintenance s coordination of a Public Institution of Higher Education, it has been found that too much information are lost when transferring the information from a group (handoffs) to another by the fact that it has not being recorded, provoking difficulties when executing many activities. This way, the present study has tried to analyze the way the processes occur in the secretary of maintenance s coordination of Pro-Rectory of Infrastructure and the way they can be simplified and/or improved, aiming the standardization and higher organizational efficiency. This study has pointed out the necessity of standardization, apart from automation in the process, aiming the improvement in services provided by this organizational department. In this sense, as the main result of this study is a Handbook of processes and routine for the secretary of maintenance s coordination of Pro-Rectory of Infrastructure of Federal University of Santa Maria/RS.